PENGARUH DAR, DER DAN TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN FARMASI - Riesta Chahya Agustina; Awan Santosa (CAPITAL: Jurnal Ekonomi dan Manajemen, 2019)
This study aims to determine the effect of debt to asset ratio, debt to equity ratio and corporate governance on financial performance in pharmaceutical sub-manufacturing manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017. The type of research used is quantitative research. The population in this study were all Pharmaceutical Manufacturing Sub-Sector Companies listed on the Indonesia Stock Exchange totaling 10 companies, while the sample for this study amounted to 8 Pharmaceutical Companies. The data collection technique in this study is to use documentation and literature study techniques. The results show, 1) debt to asset ratio does not significantly influence financial performance, 2) debt to equity ratio has a significant effect on financial performance, 3) corporate governance has a significant effect on financial performance, 4) debt to asset ratio, debt to equity ratio and corporate governance simultaneously have a significant effect on financial performance. the coefficient of determination (R2) obtained is 0.637, meaning that the ability of the independent variable to describe the dependent variable is 63.7%, while the rest (100% - 63.7% = 36.3%). 36.3% are described by other factors outside the variables in the regression equation.Keywords: Leverage Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Corporate Governance, Financial Performance